2015
DOI: 10.1111/sji.12318
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Interferon Regulatory Factor 4 Attenuates Acute Liver Allograft Rejection in Mice

Abstract: Acute liver allograft rejection is a serious complication after liver transplantation. Interferon regulatory factor 4 (IRF4) is expressed predominantly in the immune system and plays an important role in its development and function. However, the role of IRF4 in liver transplantation has never been investigated. In our current study, to evaluate the effect of IRF4 inhibition on recipient survival, IRF4 siRNA, or control siRNA, or PBS was injected into the liver allograft recipients through caudal vein. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…BET bromodomain inhibitors such as JQ1, MA4-022-1, and MA4-022-2 could be used to decrease expression and protein levels of HOXB13, resulting in suppression of tumor cell growth in castration-resistant prostate cancers [82]. Antisense oligonucleotide targeting of IRF4 suggest its promise as a therapeutic target in multiple myeloma [83], while IRF4 siRNA suggests a role for inhibiting IRF4 to improve liver transplant efficiency [84]. Small molecules 10-E-09, 12-P-16 and 13-I-18 decreased IRF4 protein levels in myeloma cells and decreased viable cell levels of a variety of myeloma cells compared to IRF4 negative cells [85].…”
Section: Additional Transcription Factor Targets Nominated By Depmap Datamentioning
confidence: 99%
“…BET bromodomain inhibitors such as JQ1, MA4-022-1, and MA4-022-2 could be used to decrease expression and protein levels of HOXB13, resulting in suppression of tumor cell growth in castration-resistant prostate cancers [82]. Antisense oligonucleotide targeting of IRF4 suggest its promise as a therapeutic target in multiple myeloma [83], while IRF4 siRNA suggests a role for inhibiting IRF4 to improve liver transplant efficiency [84]. Small molecules 10-E-09, 12-P-16 and 13-I-18 decreased IRF4 protein levels in myeloma cells and decreased viable cell levels of a variety of myeloma cells compared to IRF4 negative cells [85].…”
Section: Additional Transcription Factor Targets Nominated By Depmap Datamentioning
confidence: 99%
“…Myeloid cell-specific deletion of IRF4 is sufficient to induce inflammation (M1 polarization) and subsequent insulin resistance in the liver, skeletal muscle, and white adipose tissue (WAT) (19). However, inhibition of IRF4 by siRNA or tacrolimus attenuates acute rejection after liver transplantation by promoting M2 macrophage differentiation or improving Th17/Treg balance, respectively (88,127). These paradoxical functions of IRF4 in liver macrophage polarization can be explained by the different animal models and IRF4 inhibition strategies used.…”
Section: Interferon Regulatory Factor Signaling In the Liver Fat And Skeletal Musclementioning
confidence: 99%
“…This effect may be mediated through the TAC-NFAT-IRF4 and BATF/JUN/IRF4 complex-IL-21 axes, with the latter inhibiting IL-12-producing Tfh cells and consequently reducing liver injury [91,92]. Zhao, W. et al also demonstrated that silencing IRF4 resulted in decreased levels of inflammatory factors such as TNF-α, IL-6, and IFN-γ and induced anti-inflammatory IL-10 levels, thereby attenuating acute liver transplant rejection in mice [133]. In adult patients with acute hepatitis A caused by HAV infection, severe liver injury was observed with elevated levels of chemokines such as CXCL10, CCL4, and CCL5.…”
Section: Irfs and Post-transplantation/other Modes Of Liver Injurymentioning
confidence: 99%